Organic-inorganic hybrid material as well as preparation method and application thereof
Through transesterification reaction, the inorganic oxyacid esters are combined with polyols to form organic-inorganic hybrid materials, which solves the problem of low transparency of existing materials and realizes the preparation of materials with high refractive index and transparency, which is suitable for a variety of optical applications.
Patent Information
- Application Number
- CN202311255667.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The transparency of existing organic-inorganic hybrid materials is not high and it is difficult to meet the needs of high refractive index and transparency.
Through transesterification reaction, the inorganic oxyacid esters are combined with the polyol to form an organic-inorganic hybrid material. Inorganic elements are used to form chemical bonds in the polyol structural network to prepare materials with high refractive index and transparency.
The material has high refractive index (≥1.5) and high transparency (light transmittance ≥95%), and the material has good thermal stability and is easy to use, and is suitable for a variety of optical applications.
Smart Images

Figure CN119684343A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of materials, and in particular relates to an organic-inorganic hybrid material and a preparation method and application thereof. Background Art
[0002] The refractive index (RI) is one of the most important properties of optical materials in design and application. In recent years, the demand for high refractive index optical materials in eyeglass lenses, filters, optical adhesives, high reflective and anti-reflective coatings, and optoelectronic devices has been increasing. The refractive index of traditional polymers is relatively low, ranging from 1.3 to 1.4. In practical applications, polymer prisms used in complementary metal oxide semiconductor image sensors require a refractive index greater than 1.5, or even 1.7. In addition, many optoelectronic devices have high requirements for the refractive index, so it is necessary to design the molecules of traditional polymers to meet the needs of the application.
[0003] Inorganic materials usually have a higher refractive index (usually between 2.0-5.0). However, inorganic materials usually also have many disadvantages, such as high density (usually greater than 2.5g / cm 3 ), general transparency and low stability. Especially in the application of anti-reflective coatings, the refractive index of inorganic materials cannot be continuously adjusted, and the manufacturing process becomes more and more complicated and expensive. Compared with inorganic materials, organic materials have the advantages of low density, excellent impact resistance, good processing performance, etc. However, due to the limitations of chemical structure, most organic materials have a low refractive index of about 1.3-1.4, and the range of refractive index is not easy to adjust. Therefore, combining the advantages of inorganic and organic materials to prepare organic-inorganic hybrid materials with both high refractive index and transparency for use in different optical scenarios has very important research and high-end application significance.
[0004] Traditionally, an effective method for synthesizing these organic-inorganic hybrid materials is to add inorganic segments with high refractive index (such as titanium dioxide, zirconium dioxide, lead sulfide or zinc sulfide) to the polymer matrix at the nanoscale. However, this preparation method cannot effectively disperse the inorganic components to a high degree, resulting in a significant decrease in transparency. At the same time, this preparation method will make the later processing of the material more difficult. Summary of the invention
[0005] In view of this, the present invention provides an organic-inorganic hybrid material and a preparation method and application thereof, the main purpose of which is to solve the technical problem of low transparency of the organic-inorganic hybrid material.
[0006] In one aspect, the present invention provides an organic-inorganic hybrid material, wherein the organic-inorganic hybrid material is a material obtained by an ester exchange reaction between an inorganic oxygen-containing acid ester and a polyol.
[0007] Optionally, the inorganic elements in the organic-inorganic hybrid material participate in forming chemical bonds in the structural network formed by the polyol.
[0008] Optionally, the organic-inorganic hybrid material has a light transmittance of ≥95% and a refractive index of ≥1.5.
[0009] The material developed by the present invention has high refractive index and transparency, good thermal stability, and is easy to use. It can be widely used in organic optical materials such as eyeglass lenses, filters, optical adhesives, high-reflection and anti-reflection coatings, and optoelectronic devices.
[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned organic-inorganic hybrid material, the preparation method comprising the following steps:
[0011] The raw materials containing inorganic oxygen-containing acid esters and polyols undergo an ester exchange reaction to obtain an organic-inorganic hybrid material.
[0012] The present invention proposes a new strategy for synthesizing organic-inorganic hybrid materials by involving inorganic elements in forming chemical bonds in a structural network composed of organic polyols. No additional organic solvent is required during the synthesis process, and the reaction byproduct is high-purity ethanol, which is highly economical, green, efficient and environmentally friendly. At the same time, this integrated organic and inorganic combination method allows the material to be used to prepare a high-refractive index coating by spin coating or evaporation coating, and can also be directly cast to prepare corresponding optical devices.
[0013] Optionally, the molar ratio of the inorganic oxygen-containing acid ester to the polyol is (0.8-1.2)n 3 / x:1;
[0014] Wherein, x is the number of moles of alkoxy groups contained in each mole of inorganic oxygen-containing acid ester;
[0015] n 3 It is the number of moles of hydroxyl groups contained in each mole of polyol.
[0016] Optionally, the molar ratio of the inorganic oxygen-containing acid ester to the polyol is selected from 0.8n 3 / x, 0.85n 3 / x, 0.9n 3 / x, 0.95n 3 / x, 1n 3 / x, 1.05n 3 / x, 1.1n 3 / x, 1.15n 3 / x and 1.2n 3 / Any value in x or any range between them.
[0017] Optionally, the inorganic oxygen-containing acid ester is selected from a compound having a chemical formula shown in Formula I and / or a compound having a chemical formula shown in Formula II:
[0018] M(OR 1 ) n 1 Formula I;
[0019] O=P(OR 2 ) n 2 Formula II;
[0020] In Formula I, M is a metal element or a non-metal element excluding P, R 1 Selected from C1~C 12 At least one of the alkyl groups, n 1 =2~12;
[0021] In formula II, P is the non-metallic element phosphorus, R 2 Selected from C1~C 12 At least one of the alkyl groups, n 2 =2~12.
[0022] Optionally, in Formula I, n 1 =2, 3, 4, 5, 6, 7 or 8.
[0023] Optionally, in Formula II, n 2 =3.
[0024] Optionally, M is selected from one of B, Si, Ge, Al, Ti, Fe, Sn, V, Ga, Zr, Cr, Sb or W.
[0025] Optionally, the inorganic oxygen-containing acid ester is selected from at least one of trimethyl borate, triethyl borate, tripropyl borate, tributyl borate, tri-n-hexyl borate, tri-isooctyl borate, trioctyl borate, methyl orthosilicate, tetraethyl silicate, tetrapropyl silicate, tetrabutyl silicate, ethyl orthogermanate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tri-n-pentyl phosphate, trihexyl phosphate, aluminum triethanolate, aluminum isopropoxide, aluminum n-butoxide, aluminum tert-butoxide, tetraethyl titanate, tetraisopropyl titanate, tetrabutyl titanate, tetrahexyl titanate, tetraisooctyl titanate, tetrabutyl ferrate, tetrabutyl stannate, butyl orthovanadate, gallium ethoxide, tetra-n-propyl zirconate, tetrabutyl zirconate, tert-butyl chromate, ethyl antimonite, butyl antimonite, ethanol tungsten and isopropoxide tungsten.
[0026] Optionally, the general formula of the polyol is R 2 -(OH) x, where x ≥ 2.
[0027] Optionally, the number of hydroxyl groups in the polyol is not less than two.
[0028] Optionally, the polyol is selected from at least one of ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600, polyethylene glycol 800, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, terephthalate, glycerol, trimethylolpropane, pentaerythritol, xylitol and sorbitol.
[0029] The present invention can change the water solubility of the hybrid material by controlling the composition of the organic polyol in the hybrid material, and can be applied in different scenarios.
[0030] Optionally, the raw material containing the inorganic oxygen-containing acid ester and the polyol undergoes an ester exchange reaction in the presence of an ester exchange catalyst to obtain an organic-inorganic hybrid material.
[0031] Optionally, the added amount of the transesterification catalyst is 0.1 wt% to 5 wt% of the inorganic oxygen-containing acid ester.
[0032] Optionally, the amount of the ester exchange catalyst added is the mass percentage of the inorganic oxygen-containing acid ester selected from any value among 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% and 5.0wt%, or any range value between two of them.
[0033] Optionally, the transesterification catalyst is selected from an acidic catalyst and / or a basic catalyst.
[0034] Optionally, the acidic catalyst is selected from at least one of an alcohol-soluble acid, a solid acid, an alkoxyaluminum, a phenoxyaluminum, tetrabutyl stannate, an alkoxytitanium, an alkoxyzirconium, ethyl antimonite and butyl antimonite.
[0035] Optionally, the alkaline catalyst is selected from alcohol-soluble bases and / or solid bases.
[0036] Optionally, the alcohol-soluble acid is an acid that is readily soluble in alcohol.
[0037] Optionally, the alcohol-soluble base is a base that is readily soluble in alcohol.
[0038] Optionally, the alcohol-soluble acid includes sulfuric acid, sulfonic acid, and the like.
[0039] Optionally, the alcohol-soluble base includes NaOH, KOH, NaOCH3, an organic base, etc.
[0040] Optionally, the ester exchange reaction catalyst is: alkaline catalyst including alkalis that are easily soluble in alcohol (such as NaOH, KOH, NaOCH3, organic bases, etc.) and various solid base catalysts, acidic catalyst including acids that are easily soluble in alcohol (such as sulfuric acid, sulfonic acid, etc.) and various solid acid catalysts, alkoxy aluminum, phenoxy aluminum, tetrabutyl stannate, alkoxy titanium, alkoxy zirconium, ethyl antimonite, butyl antimonite, etc., and the catalyst dosage is 0.1wt% to 5wt% of the inorganic oxygen-containing acid ester.
[0041] Optionally, the conditions for the transesterification reaction include: a reaction temperature of 80 to 180° C., a reaction time of 2 to 10 hours, and an inert reaction atmosphere.
[0042] Optionally, the inert atmosphere is selected from at least one of nitrogen and an inert gas.
[0043] Optionally, the reaction temperature is selected from any value of 80°C, 85°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 175°C and 180°C, or any range therebetween.
[0044] Optionally, the reaction time is selected from any value among 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, or any range therebetween.
[0045] Optionally, the conversion rate of the transesterification is between 60% and 80%.
[0046] Optionally, the transesterification reaction is followed by reduced pressure distillation.
[0047] Optionally, the conditions for the reduced pressure distillation include: vacuum degree of 0.01 to 5 KPa, temperature of 170 to 230° C., and reaction time of 0.5 to 5 h.
[0048] Optionally, during the reduced pressure distillation process, the vacuum degree of the system is selected from any value among 0.01 KPa, 0.02 KPa, 0.05 KPa, 0.1 KPa, 0.5 KPa, 1 KPa, 2 KPa, 3 KPa, 4 KPa, 4.5 KPa, 5 KPa or any range value between any two of them.
[0049] Optionally, during the reduced pressure distillation process, the reaction temperature is selected from any value of 170°C, 1175°C, 180°C, 190°C, 200°C, 210°C, 220°C, 225°C, 230°C or any range between two thereof.
[0050] Optionally, during the reduced pressure distillation process, the reaction time is selected from any value of 0.5 hour, 0.8 hour, 1 hour, 2 hours, 3 hours, 4 hours, 4.5 hours, 5 hours, or any range value therebetween.
[0051] Optionally, the conversion rate of the transesterification reaction after the reduced pressure distillation is greater than 90%.
[0052] Optionally, the inorganic oxygen-containing acid ester and the polyol undergo an ester exchange reaction under stirring.
[0053] The present invention provides a specific embodiment, the preparation method of the organic-inorganic hybrid material: a) mixing an inorganic oxygen-containing acid ester, a polyol and an ester exchange reaction catalyst, performing an ester exchange reaction under stirring, passing an inert atmosphere for protection, the reaction temperature is between 80 and 180° C., and the reaction time is between 2 and 10 hours;
[0054] b) performing reduced pressure distillation after the reaction in step a), controlling the vacuum degree of the system to be between 0.01 and 5 KPa, the reaction temperature to be between 170 and 230° C., and the reaction time to be between 0.5 and 5 hours.
[0055] In the present invention, "C1 to C8" and the like refer to the number of carbon atoms contained in the group.
[0056] In the present invention, "alkyl" is a group formed by losing any hydrogen atom from an alkane compound molecule.
[0057] In a third aspect, the present invention provides the use of the above organic-inorganic hybrid material in the preparation of eyeglass lenses, filters, optical adhesives, high-reflection and anti-reflection coatings, optoelectronic devices, and light-emitting diode packaging materials.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] (1) The organic-inorganic hybrid material with high refractive index and transparency provided by the present invention has high transparency in the visible light region, with a transmittance higher than 95% and a refractive index greater than 1.5.
[0060] (2) The present invention uses a class of organic-inorganic hybrid materials as optical materials with high refractive index and transparency, which can be widely used in eyeglass lenses, filters, optical adhesives, high-reflection and anti-reflection coatings and optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 The UV-Vis spectra of the products synthesized in Examples 1-5 of the present invention;
[0062] Figure 2 A coating prepared by spin coating of the product synthesized in Examples 1-5 of the present invention;
[0063] Figure 3 It is a cast product of the product synthesized in Example 3 of the present invention. DETAILED DESCRIPTION
[0064] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0065] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0066] The analysis method in the embodiment of the present invention is as follows:
[0067] The visible-ultraviolet transmission spectrum analysis was performed using a UV-visible spectrometer model CARY-5000 produced by VARIAN.
[0068] The refractive index analysis was performed using a fully automatic Abbe refractometer, model HM-ZG30, produced by Hengmei Company.
[0069] According to one embodiment of the present invention, the synthesis method of the above-mentioned organic-inorganic hybrid material with high refractive index and transparency comprises the following steps:
[0070] a) Inorganic oxygen-containing acid ester, polyol and transesterification catalyst are uniformly mixed in a three-necked flask, and transesterification reaction is carried out under stirring, and then a distillation device is connected and nitrogen is passed through for protection. The reaction temperature is between 80 and 180° C., the reaction time is between 2 and 10 hours, and the conversion rate of the transesterification reaction is between 60% and 80%.
[0071] b) connecting the device after the reaction in step a) to a water pump or an oil pump for vacuum distillation to make the transesterification reaction more complete, controlling the vacuum degree of the system to be between 0.01 and 5 KPa, the reaction temperature to be between 170 and 230° C., the reaction time to be between 0.5 and 5 hours, and the conversion rate of the transesterification reaction to be greater than 90%.
[0072] The organic-inorganic hybrid material with high refractive index and transparency prepared by the present invention can be used to prepare a coating with high refractive index and transparency by a spin coating or evaporation coating method, and can also be directly cast to prepare a corresponding optical device.
[0073] Example 1
[0074] Add 10g 1,4-cyclohexanediol, 8g ethyl orthosilicate and 3g tetraethyl titanate into a three-necked flask, connect a distillation device, add 0.01g ethyl antimonite as a catalyst under stirring, heat to 120℃ under nitrogen protection, and react for 8 hours. A large amount of ethanol is distilled out during this process, and the conversion rate of the transesterification reaction is 71%; then connect a vacuum device, react under reduced pressure distillation conditions, control the vacuum degree of the system at 0.5KPa, and heat to 175℃. After 1 hour of reaction, stop the reaction, cool naturally to room temperature, take out the sample, and the conversion rate of the transesterification reaction is 95%. After the reaction, prepare the coating by spin coating. The product has a visible light transmittance of 98% and a refractive index of 1.5.
[0075] Example 2
[0076] Add 20g 1,4-cyclohexanedimethanol and 8g tetra-n-propyl zirconate into a three-necked flask, where tetra-n-propyl zirconate is used as both an inorganic oxygen acid salt raw material and an ester exchange catalyst. Connect a distillation device, heat to 150°C under stirring and nitrogen protection, react for 4 hours, and the conversion rate of the ester exchange reaction is 80%; then connect a vacuum device, react under reduced pressure distillation conditions, control the system vacuum degree at 0.05KPa, and heat to 185°C. After 3 hours of reaction, stop the reaction, cool naturally to room temperature, take out the sample, and the conversion rate of the ester exchange reaction is 95%. After the reaction, a coating is prepared by a spin coating method. The product has a visible light transmittance of 97% and a refractive index of 1.7.
[0077] Example 3
[0078] Add 10g of terephthalic acid and 5g of triethoxyaluminum into a three-necked flask, connect a distillation device, drop 0.2g of isopropyl titanate as a catalyst under stirring, heat to 150°C under nitrogen protection, react for 4 hours, and the conversion rate of transesterification reaction is 72%; then connect a vacuum device, react under reduced pressure distillation conditions, control the vacuum degree of the system at 0.2KPa, and heat to 200°C. After reacting for 2 hours, stop the reaction, cool naturally to room temperature, take out the sample, and the conversion rate of transesterification reaction is 93%. After the reaction, prepare the coating and block material by spin coating and direct casting. The product has a visible light transmittance of 95% and a refractive index of 1.6.
[0079] Embodiment 4 to Embodiment 13
[0080] The specific ingredient types, materials and reaction conditions are shown in Table 1 below. Other operations during the synthesis process are the same as in Example 1.
[0081] Table 1. Raw material composition, ratio, transmittance and refractive index of Examples 4 to 13
[0082]
[0083] From the experimental data in Table 1 and Figure 1 It can be seen that the light transmittance of the organic-inorganic hybrid material prepared by the present invention is 95% to 99%, and the refractive index is 1.5 to 1.9; Figure 2 and Figure 3 The actual product shows that the product of the present invention has high transparency and can be widely used in eyeglass lenses, filters, optical adhesives, high-reflection and anti-reflection coatings and optoelectronic devices.
[0084] Comparative Example
[0085] Traditional organic-inorganic hybrid materials are prepared by the sol-gel method, in which inorganic segments with high refractive index (such as titanium dioxide, zirconium dioxide, lead sulfide or zinc sulfide, etc.) are doped into a polymer (such as organosilane) matrix network at the nanoscale to obtain organic-inorganic hybrid materials.
[0086] In the above-mentioned traditional technologies, inorganic material monomers do not participate in the formation of effective chemical bonds, and the composite materials are mostly amorphous with a low refractive index. In addition, internal stress is easily generated inside the composite materials prepared by the sol-gel method through heat treatment, which will result in the higher the content of inorganic particles, the worse the mechanical properties of the composite materials.
[0087] The test results show that the refractive index of traditional organic-inorganic hybrid materials is about 1.3, the transmittance is about 80% to 90%, and the mechanical properties are poor.
[0088] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. An organic-inorganic hybrid material, characterized in that: The organic-inorganic hybrid material is a material obtained by an ester exchange reaction between an inorganic oxygen-containing acid ester and a polyol.
2. An organic-inorganic hybrid material according to claim 1, characterized in that: The inorganic elements in the organic-inorganic hybrid material participate in forming chemical bonds in the structural network formed by the polyol; Preferably, the light transmittance of the organic-inorganic hybrid material is ≥95%, and the refractive index is ≥1.
5.
3. The method for preparing an organic-inorganic hybrid material according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: The raw materials containing inorganic oxygen-containing acid esters and polyols undergo an ester exchange reaction to obtain an organic-inorganic hybrid material.
4. The method for preparing an organic-inorganic hybrid material according to claim 3, characterized in that: The molar ratio of the inorganic oxygen-containing acid ester to the polyol is (0.8 to 1.2) 3 / x:1; Wherein, x is the number of moles of alkoxy groups contained in each mole of inorganic oxygen-containing acid ester; n 3 It is the number of moles of hydroxyl groups contained in each mole of polyol.
5. The method for preparing an organic-inorganic hybrid material according to claim 3, characterized in that: The inorganic oxygen-containing acid ester is selected from a compound having a chemical formula shown in Formula I and / or a compound having a chemical formula shown in Formula II: M(OR 1 ) n 1 Formula I; O=P(OR 2 ) n 2 Formula II; In Formula I, M is a metal element or a non-metal element excluding P, R 1 Selected from C1~C 12 At least one of the alkyl groups, n 1 =2~12; In formula II, P is the non-metallic element phosphorus, R 2 Selected from C1~C 12 At least one of the alkyl groups, n 2 =2~12.
6. The method for preparing an organic-inorganic hybrid material according to claim 5, characterized in that: The M is selected from one of B, Si, Ge, Al, Ti, Fe, Sn, V, Ga, Zr, Cr, Sb or W; Preferably, the inorganic oxygen-containing acid ester is selected from at least one of trimethyl borate, triethyl borate, tripropyl borate, tributyl borate, tri-n-hexyl borate, tri-isooctyl borate, trioctyl borate, methyl orthosilicate, tetraethyl silicate, tetrapropyl silicate, tetrabutyl silicate, ethyl orthogermanate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tri-n-pentyl phosphate, trihexyl phosphate, aluminum triethoxide, aluminum isopropoxide, aluminum n-butoxide, aluminum tert-butoxide, tetraethyl titanate, tetraisopropyl titanate, tetrabutyl titanate, tetrahexyl titanate, tetraisooctyl titanate, tetrabutyl ferrate, tetrabutyl stannate, butyl orthovanadate, gallium ethoxide, tetra-n-propyl zirconate, tetrabutyl zirconate, tert-butyl chromate, ethyl antimonite, butyl antimonite, tungsten ethoxide and tungsten isopropoxide.
7. The method for preparing an organic-inorganic hybrid material according to claim 3, characterized in that: The number of hydroxyl groups in the polyol is not less than two; Preferably, the polyol is selected from at least one of ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600, polyethylene glycol 800, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, terephthalate, glycerol, trimethylolpropane, pentaerythritol, xylitol and sorbitol.
8. The method for preparing an organic-inorganic hybrid material according to claim 3, characterized in that: The raw materials containing inorganic oxygen-containing acid esters and polyols are subjected to an ester exchange reaction in the presence of an ester exchange catalyst to obtain an organic-inorganic hybrid material; Preferably, the added amount of the transesterification catalyst is 0.1wt% to 5wt% of the inorganic oxygen-containing acid ester; Preferably, the transesterification catalyst is selected from an acidic catalyst and / or a basic catalyst; Preferably, the acidic catalyst is selected from at least one of an alcohol-soluble acid, a solid acid, an alkoxyaluminum, a phenoxyaluminum, tetrabutyl stannate, an alkoxytitanium, an alkoxyzirconium, ethyl antimonite and butyl antimonite; The alkaline catalyst is selected from alcohol-soluble bases and / or solid bases.
9. The method for preparing an organic-inorganic hybrid material according to claim 3, characterized in that: The conditions of the transesterification reaction include: a reaction temperature of 80 to 180° C., a reaction time of 2 to 10 hours, and a reaction atmosphere of an inert atmosphere; Preferably, the transesterification reaction is followed by vacuum distillation; Preferably, the conditions of the reduced pressure distillation include: vacuum degree of 0.01-5KPa, temperature of 170-230°C, and reaction time of 0.5-5h; Preferably, the inorganic oxygen-containing acid ester and the polyol undergo an ester exchange reaction under stirring.
10. Use of an organic-inorganic hybrid material according to any one of claims 1 to 2 in the preparation of eyeglass lenses, optical filters, optical adhesives, high-reflection and anti-reflection coatings, optoelectronic devices, and light-emitting diode packaging materials.
Citation Information
Patent Citations
Organic-inorganic hybrid ultraviolet absorption material as well as preparation method and application thereof
CN111904885A